Optimization of multi effect evaporation systems using a metaheuristic hybrid algorithm - UZDİYEM, Orhun; ÖZÇELİK, Yavuz (MANAS journal of engineering, 2021)
A computer program, capable of carrying out the mathematical modelling and optimization of multi effect evaporation (MEE) systems is developed in the scope of this study. C# programming language is used in the development of the computer program. A Particle Swarm Optimization (PSO) based algorithm is developed and hybridized with a Levenberg-Marquardt (LM) based algorithm. A computer program interface is developed in .NET platform for the user to give inputs such as feed and product streams flowrate and concetration. The optimization results is represented through this interface. Concentrating the sodium hydroxide content in the wastewater of the mercerization process is selected as the sample case.